The Influence of Social Media Marketing Towards Fast Fashion Brands - Prameswari, Citragama (Jurnal Entrepreneur dan Entrepreneurship, 2022)
Abstract Fast-fashion brands have significantly risen in the business industry, an impetus is also needed to increase the company’s growth. The purpose of this paper is to examine how social media marketing influences customers and has a significant effect on their purchase intentions, also willingness to pay for fast fashion brands. This study confirms that social media marketing provides insights into envisioning brand loyalty. Thus, creating effective and strategic social media marketing is crucial. The questionnaire was administered to a convenience sample of 244 fast fashion brands’ customers who are active in social media, was analyzed using Partial Least Square (PLS), and measured using Structural Equation Modelling (SEM). Keywords: Social Media Marketing, Willingness To Pay, Purchase Intentions, Brand Loyalty